2014
DOI: 10.1186/1471-2458-14-68
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing tobacco use treatment patterns among Vietnamese health care providers working in community health centers

Abstract: BackgroundAlmost half of adult men in Viet Nam are current smokers, a smoking prevalence that is the second highest among South East Asian countries (SEAC). Although Viet Nam has a strong public health delivery system, according to the 2010 Global Adult Tobacco Survey, services to treat tobacco dependence are not readily available to smokers. The purpose of this study was to characterize current tobacco use treatment patterns among Vietnamese health care providers and factors influencing adherence to guideline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 19 publications
0
19
0
Order By: Relevance
“…Notably, health care providers appear to support a VHW role in treating tobacco use. A survey of health care providers in 23 CHCs in Hanoi found that 90% strongly agreed that they would refer patients to a trained VHW for smoking cessation treatment, and 84% strongly agreed that VHWs could be trained to provide counseling [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, health care providers appear to support a VHW role in treating tobacco use. A survey of health care providers in 23 CHCs in Hanoi found that 90% strongly agreed that they would refer patients to a trained VHW for smoking cessation treatment, and 84% strongly agreed that VHWs could be trained to provide counseling [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on several prior studies (Leitlein, Smit, de Vries, & Hoving, 2013;Shelley et al, 2014), both workplace and nurse factors are known to influence the provision of smoking cessation services. Workplace factors known to influence smoking cessation services include the number of employees (Sindhu, Konggumnerd, & Wiwattanacheewin, 2014), number of smoking employees (Sarna et al, 2009), perceived organizational support (Davies, Edwards, Ploeg, & Virani, 2008), organizational policy (Braun et al, 2004), and number of health care providers (Sukbua, Kalampakorn, Kaewpan, & Powwattana, 2009).…”
Section: Variables Related To Smoking Cessation Services Provided By mentioning
confidence: 99%
“…In a study in Vietnam, some of the providers’ characteristics were found influencing tobacco use treatment. [ 18 ] These characteristics were older age of physicians, attitudes, self efficacy, and normative beliefs. [ 18 ] The barriers identified in the same study were lack of training, resources for referral, staff support, and patients’ interest in quitting.…”
Section: Discussionmentioning
confidence: 99%